Sulfidation roasting of lead and zinc carbonate with sulphur by temperature gradient method - Zheng, Yong-xing; Liu, Wei; Qin, Wen-qing; Jiao, Fen; Han, Jun-wei; Yang, Kang; Luo, Hong-lin (Journal of Central South University, 2015)
In order to enhance the lead and zinc recovery from the refractory Pb-Zn oxide ore, a new technology was developed based on sulfidation roasting with sulphur by temperature gradient method. The solid-liquid reaction system was established and the sulfidation thermodynamics of lead and zinc carbonate was calculated with the software HSC 5.0. The effects of roasting temperature, molar ratio of sulphur to lead and zinc carbonate and reaction time in the first step roasting, and holding temperature and time in the second roasting on the sulfidation extent were studied at a laboratory-scale. The experimental results show that the sulfidation extents of lead and zinc are 96.50% and 97.29% under the optimal conditions, respectively, and the artificial galena, sphalerite and wurtzite were formed. By the novel sulfidizing process, it is expected that the sulphides can be recovered by conventional flotation technology.